Vitellogenin and vitellogenin receptor gene expression is associated with male and female parenting in a subsocial insect - Roy-Zokan, Eileen M. (Proc Biol Sci, 2015)
Complex social behaviour in Hymenoptera has been hypothesized to evolve by co-opting reproductive pathways (the ovarian ground plan hypothesis, OGPH) and gene networks (the reproductive ground plan hypothesis, RGPH). In support of these hypotheses, in eusocial Hymenoptera where there is reproductive division of labour, the yolk precursor protein vitellogenin (Vg) influences the expression of worker social behaviour. We suggest that co-opting genes involved in reproduction may occur more generally than just in the evolution of eusociality; i.e. underlie earlier stages of social evolution such as the evolution of parental care, given that reproduction and parental care rarely overlap. We therefore examined vitellogenin (vg) gene expression associated with parental care in the subsocial beetle Nicrophorus vespilloides. We found a significant reduction in the expression of vg and its receptor, vgr, in head tissue during active parental care, and confirmed that the receptor is expressed in the brains of both sexes. Ours is the first study to show that vgr is expressed in the brain of a non-eusocial insect. Given the association between behaviour and gene expression in both sexes, and the presence of vitellogenin receptors in the brain, we suggest that Vg was co-opted early in the evolution of sociality to have a regulatory function. This extends the association of Vg in parenting to subsocial species and outside of the Hymenoptera, and supports the hypothesis that the OGPH is general and that heterochrony in gene expression is important in the evolution of social behaviour and precedes subsequent evolutionary specialization of social roles.